Crystal structure of di-μ-chloroacetato-hexakis(dimethylformamide)tetrakis(μ-N,2-dioxidobenzene-1-carboximidato)tetramanganese(III)disodium dimethylformamide disolvate - Daly, Connor I. (Acta Crystallogr Sect E Struct Rep Online, 2014)
The synthesis, crystal structure, and FT–IR data for the title compound, [Na(2)Mn(4)(C(2)H(2)ClO(2))(2)(C(7)H(4)NO(3))(4)(C(3)H(7)NO)(6)]·2C(3)H(7)NO or Na(2)(O(2)CCH(2)Cl)(2)[12-MC(Mn(III)) (N(shi))-4](DMF)(6)·2DMF, where MC is metallacrown, shi(3−) is salicylhydroximate, and DMF is N,N-dimethylformamide, is reported. The macrocyclic metallacrown consists of an –[Mn(III)—N—O](4)– ring repeat unit and the metallacrown captures two Na(+) ions in the central cavity above and below the plane of the metallacrown. Each Na(+) ion is seven-coordinate and is bridged to two ring Mn(III) ions, through either a coordinating DMF molecule or a chloroacetate anion. The ring Mn(III) ions have either a tetragonally distorted octahedral geometry or a distorted square-pyramidal geometry. Weak C—H⋯O interactions, in addition to pure van der Waals forces, contribute to the overall packing of the molecules. The complete molecule has inversion symmetry and is disordered over two sets of sites with an occupancy ratio of 0.8783 (7):0.1217 (7). The solvent molecule is also disordered over two sets of sites, with an occupancy ratio of 0.615 (5):0.385 (5).